Innovation tree - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A participatory rural appraisal tool to help people visualize and analyze the way in which an innovation is spread over time between community members. It distinguishes innovators, and early and late adopters. It is also a way of helping both outsiders and the community to understand some of the social and psychological dimensions that influence the adoption and diffusion of an innovation within that community. The innovation tree investigates how different personalities or types of innovators play a different role in promoting the technology.